Requirements, domain and specifications: a viewpoint-based approach to requirements engineering - Silva, Andrés (Proceedings - International Conference on Software Engineering, 2002)
Viewpoint-based Requirements Engineering (VBRE) is based on the fact that there is a multiplicity of stakeholders that take part in any requirements process. This will inevitably lead to conflicts and inconsistencies that, if adequately managed, can be used to improve the process, as they are sources of requirements. There comes a time in every VBRE process when different viewpoints need to be compared to fin discrepancies (conflicts, inconsistencies). But in Requirements Engineering (RE) we also deal with other categories of statements, apart from "requirements", like domain descriptions and interface specifications. We could use this categorization to (i) internally classify the contents of each viewpoint by categories; (ii) compare the contents of one viewpoint against another, taking into account that this comparison should only be made between elements of the same category; (iii) classify the discrepancies by the affected categories and (iv) generate resolutions for the discrepancies according to this classification. In this paper, we present a VBRE method based on this approach, which is not constrained to a particular representation formalism. The proposed framework includes discrepancy detection and classification and solution generation.